2014
DOI: 10.7482/0003-9438-57-021
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of infrared temperature measurements for continuous temperature monitoring in gilts

Abstract: The aim of this study was to evaluate whether an infrared thermometer, a pyrometer, could detect the body surface temperature in the orbital area of gilts without contacting them. Furthermore, it was tested whether an increase in the gilts' temperatures could be detected. Therefore, fever was induced. During 11 trials, 43 German Landrace gilts were injected with either a Porcilis AR-T DF (Intervet International B.V., Boxmeer, Netherlands) vaccine or 2 ml of 0.9 % NaCl. A commercial temperature logger (TRIX-8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Pro-inflammatory mediators and especially (IL-1β and IL-6) were reported to enhance leukocyte transmigration into the site of infection by favouring expression of cell adhesion molecules and production of eicosanoids and prostaglandins that perpetuate the inflammatory cascade in septicemia (Praveena et al, 2010). The higher levels of (IL-1β and IL-6) cytokines in the mice serum in this research work could also be attributed to fever, anorexia and behavioural changes observed in the infected animals (Dionissopoulos et al, 2012;Gyenai et al, 2012;Schmidt et al, 2014). The increased in serum cytokine levels of pro-inflammatory cytokines (IL-1β and IL-6) at 120 h post-inoculation could perchance be due to the damage of the tissue cells and infiltration of inflammatory cells into the sites of infections.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Pro-inflammatory mediators and especially (IL-1β and IL-6) were reported to enhance leukocyte transmigration into the site of infection by favouring expression of cell adhesion molecules and production of eicosanoids and prostaglandins that perpetuate the inflammatory cascade in septicemia (Praveena et al, 2010). The higher levels of (IL-1β and IL-6) cytokines in the mice serum in this research work could also be attributed to fever, anorexia and behavioural changes observed in the infected animals (Dionissopoulos et al, 2012;Gyenai et al, 2012;Schmidt et al, 2014). The increased in serum cytokine levels of pro-inflammatory cytokines (IL-1β and IL-6) at 120 h post-inoculation could perchance be due to the damage of the tissue cells and infiltration of inflammatory cells into the sites of infections.…”
Section: Discussionmentioning
confidence: 51%
“…There were increases in the concentration of IL-6 with 0.4 mL of 10 3 cfu in the mice that were inoculated orally with Pasteurella multocida type B: 2 compared with those inoculated with LPS and the control group. Schmidt et al (2014) observed that single intravenous injection of LPS was tolerated easily by mice without any observable pathology or evidence of ill health. They also stated that repeated intraperitoneal injections of LPS in mice at 8 h intervals caused the mice to become ill (Schmidt et al, 2014) exhibiting reduced social and feeding activity, huddling behavior with piloerection and shivering, increased skin turgor and weight loss and eventually led to hypothermia before the mice became moribund.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…sensor was not described [two studies on thermal cameras (47,48), one on load cells with RFID in a feeding station (49), one on cameras (50), and one on microphone ( 51)]. From the obtained list of commercially available PLF technologies, 14% were validated in some identified papers of literature search (12 of 83 technologies), of which 5% corresponded to external validation (52)(53)(54)(55).…”
Section: Non-contact Body-temperature Sensorsmentioning
confidence: 99%
“…Also, the usefulness of thermal image to assess piglets' stress by measuring bodytemperature changes when applying stressors (cold, pain, hunger, thirst) was tested (89). One study was found using a pyrometer for continuously measuring body-temperature, showing negative validation results (55). Load cells (scales) with and without RFID were validated for assessing body weight.…”
Section: Physical Conditionmentioning
confidence: 99%